Looking beyond in Sleep Medicine Practice: Effect of OSA Management in Floppy Eyelid Syndrome – A Case Report - Bolouki-Azari, Helya; Soleimani, Arman; Najafi, Arezu; Amirifard, Hamed (Sleep Science, 2024)
Obstructive Sleep Apnea Syndrome (OSA) is a common sleep disorder characterized by recurrent episodes of partial or complete upper airway obstruction during sleep. Floppy Eye Syndrome (FES) is a condition in which the upper eyelids easily evert with upward traction due to underlying tarsal plate laxity and is associated with chronic, reactive papillary conjunctivitis; this causes the eye to be vulnerable to discomfort and visual symptoms. A 49-year-old man with an 8-year history of snoring, sleep fragmentation, and daytime sleepiness was admitted as an outpatient in our sleep clinic. The patient had complied ocular symptoms such as burning eyes, redness, and irritative ocular symptoms in the past five years, arising upon waking up. The symptoms did not regress with the use of artificial tears and proper ointment. The patient was diagnosed with OSA and began using continuous positive airway pressure (CPAP). CPAP therapy significantly corrected the symptoms of FES associated with OSA . This would help to sensibilize ocular findings in patients with OSA and identify hidden sleeping diseases needing a more appropriate investigation and possible treatment. We must look beyond our approach to sleep clinic patients and avoid being kept to the common symptoms patients represent.
Keywords: post intensive care syndrome; OSA; floppy eyelid syndrome; FES; sleep; CPAP